MAGIC FOR CINDERELLA: PROCEDURES OF MEASUREMENT IN HUMANITARIAN RESEARCH - Irina V. Melik-Gaykazyan (Высшее образование в России)
The problem of metaphorical understanding and measurement procedures application is still actual for humanitarian sciences. This conclusion is based on an overview of articles dealing with the interpretations of measurements for humanitarian research and with their practical realization. The papers were published in the journal «Tomsk State Pedagogical University Bulletin». This journal publishes the articles across the whole spectrum of humanitarian sciences and presents itself as a common Russian edition which allows to conclude about the established practice in Russian investigations. In the considered papers measurements are an analogy with the semiotic diagnostics of the studied processes. If one accepts the fact that the semiotic processes are a special case of information processes, the natural science procedures application for measurements of information characteristics (value and effectiveness) becomes possible in humanitarian research.